MENCEGAH PENYAKIT MELALUI PERILAKU HIDUP BERSIH DAN SEHAT SERTA PEMANFAATAN TANAMAN OBAT KELUARGA - Heni Aguspita Dewi; R Siti Jundiah; Tuti Suprapti; Purwanti Purwanti; Dhien Novita Sani (Jurnal Pengabdian Masyarakat (Jupemas), 2022)
Bhakti Kencana University in collaboration with Kutawarinign Village held Community Service through Real Work Lectures (KKN). It is carried out in a hybrid way, namely offline and online with the target community of Kp. Bojong Koneng. Various things are suggested as an effort to increase public understanding regarding Clean and Healthy Life Behavior (PHBS) prevention of diseases by rodents and the use of herbal plants. Several agendas were carried out, including health promotion in the form of counseling on PHBS and Prevention of Diseases caused by rodents and knowledge about Family Medicinal Plants (TOGA). A pretest and post-test were also given to the community with the aim of measuring how far the public's understanding of the material was. Judging from the community's response after the presentation of the material, there was an increase in public knowledge about PHBS prevention of diseases caused by rodents and family medicinal plants.